Folic Acid Attenuates Contrast-Induced Nephropathy in Patients With Hyperhomocysteinemia Undergoing Coronary Catheterization: A Randomized Controlled Trial - Peng, Long; Shui, Xing; Tan, Fang; Li, Zexiong; Ling, Yesheng; Wu, Bingyuan; Chen, Lin; Li, Suhua; Peng, Hui (Frontiers in Cardiovascular Medicine, 2021)
Background: Hyperhomocysteinemia is a risk factor for contrast-induced nephropathy. Folic acid can attenuate such nephropathies in rats. The protective effect of folic acid against contrast-induced nephropathy has not been studied in humans. We aimed to investigate the effect of folic acid on the incidence of contrast-induced nephropathy (CIN) after coronary catheterization in patients with hyperhomocysteinemia. Methods: This was a single-center, prospective, double-blind, randomized controlled trial (ClinicalTrials.gov, NCT02444013). In total, 412 patients (mean age: 65 ± 12 years, 268 male) with plasma homocysteine ≥15 μM, who underwent coronary arteriography (CAG) or percutaneous coronary intervention (PCI) from May 2015 to August 2018, were enrolled. Patients were randomly assigned to two groups: a treatment group (n = 203), taking 5 mg of folic acid (orally, three times/day) immediately after enrollment and for 72 h after operation, and a control group (n = 209), taking placebo. Contrast-induced nephropathy was defined as an increase in serum creatinine of >25% or 44 μM within 48 or 72 h after contrast medium administration. Results: In total, 50 (12%) patients developed CIN after 48 h after catheterization, including 16 (8%) in the treatment group and 34 (16%) in the control group (P = 0.009). Meanwhile, 53 (13%) patients developed CIN after 72 h of CAG/PCI, including 18 (9%) in the treatment group and 35 (17%) in the control group (P = 0.017). The incidence of contrast-induced nephropathy in the treatment group was lower than that in the control group (P = 0.017). Logistic regression analysis confirmed that administration of folic acid was a protective factor against contrast-induced nephropathy (RD = 0.0788, 95%CI: 0.0105–0.1469, P = 0.019). We found no serious adverse events associated with folic acid. No death or hemodialysis occurred in either group. Conclusions: Perioperative administration of folic acid attenuates the incidence of contrast-induced nephropathy after coronary catheterization in patients with hyperhomocysteinemia. Clinical Trial Registration:ClinicalTrials.gov, identifier [NCT02444013].